Implementasi Peraturan Daerah Kabupaten Tangerang Nomor 2 Tahun 2010 Tentang Pnegawasan Dan Pengendalian LingkunganHidup Di Kecamatan Cikupa - ANGGIANA RUSNIA, SITI; Sjafari, Agus; Riswanda (LPPM STIA Banten, 2024)
Environmental damage can be detrimental to the government and society such as damage to public infrastructure that is usually used by the community such as roads, places of worship, and educational facilities. the purpose of the research is to find out the Implementation of Tangerang Regency Regional Regulation Number 2 of 2010 concerning Environmental Supervision and Control in Cikupa District. The theory used is according to Edwards III's view consisting of communication, resources, disposition, and bureaucratic structure. The research method uses qualitative research with a descriptive approach. Data collection techniques using interviews, observation & documentation studies. The findings in the field show that communication between organizations & implementing activities is not optimal, due to the tug of interest between the Tangerang Regency government and the Central Government. The resources of the flood control system in Cikupa Sub-district are not optimal, because the human resources available for maintaining flood control infrastructure are still lacking. The attitude / tendency of the implementers is not optimal because the community / village parties' proposals submitted to the Cidanau-Ciujung-Cidurian BBWS are difficult to realize, the bureaucratic structure in the implementation of the flood control system in Cikupa Subdistrict is not optimal, because the implementers work based on their respective main tasks & functions so that the commands / orders between the implementers involved are not synchronized. Keywords: Policy Implementation, Regional Regulation, Environment